Refractory Coating Technology: A Review: Coating Technology - Omidiji, Babatunde Victor; Ajewole, Raphael; Oluwajobi, Akinjide (Ife Journal of Technology, 2024)
Application of refractory coatings in foundry is very essential as they significantly enhance the surface finish of castings. Coatings applied on mould cavities, cores or patterns (as in lost foam casting) fill the tiny spaces in between the mould sand particles, solidify and render the mould surfaces smooth before pouring the liquid metal. The resulting enhancement of the surface finish of the casting has brought about an indisputable conclusion that there can be no acceptable casting without the application of refractory coatings. The casting production is considered as a backbone and influencer of the development of global economy as the level of industrialisation in each country is a reflection of the practical attention given to casting production. The demand for casting products has been on the increase over the years leading to increase in demand for refractory coatings. The indispensability of refractory coatings in casting production necessitates understanding the nitty-gritty of coating production technology which expectedly calls for a comprehensive review. The information provided in this study would undoubtedly serve as a handy summary of refractory coating production in relation to casting surface finish enhancement.